Análise pelo Supply Chain Management da cadeia produtiva da castanha de caju no Rio Grande do Norte - Amyot, Danelle (2009)
This work presents the cashew nuts chain in the State of Rio Grande do Norte between 1960 and 2009. The main purpose of this research was to find the reason of the low productivity of the cashew nut in this state, identifying in the cashew's chain production the struggling points which were limiting the commerce of this product through the distribution network. Therefore, the Supply Chain Management was used as a logistic analysis methodology, focusing on relationships management between the nodes of this chain, from the producer until the final customer. Many problems were found: first, the precarious production conditions of the small producer don't lead to reach the demanded productivity by the market. The distance, the lack of communication of the small producers among themselves and an archaic way of dealing with their businesses, may be an explanatory reason for this problem, considering that those factors are the main elements which contribute for the weakening of the small producer placed in the productive chain. Another spotted point was that the business-oriented relationship between the producer and the local trader does not allow the small producer's economical development, which interferes in any technological investment to reach a good quality production that fulfills the market demand. And also, the fact that there is a tendency of the final costumer to require lower prices day-byday, forcing a pressure on the nodes transferring to the other and successively until arriving at the producer who inevitably is suffering the biggest impacts from this mentioned pressure.